2002
DOI: 10.1016/s1097-2765(02)00469-0
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Induced Negative Selection of Thymocytes Activates Transcription of an NF-ΚB Inhibitor

Abstract: Negative selection eliminates thymocytes bearing autoreactive T cell receptors (TCR) via an apoptotic mechanism. We have cloned an inhibitor of NF-kappa B, I kappa BNS, which is rapidly expressed upon TCR-triggered but not dexamethasone- or gamma irradiation-stimulated thymocyte death. The predicted protein contains seven ankyrin repeats and is homologous to I kappa B family members. In class I and class II MHC-restricted TCR transgenic mice, transcription of I kappa BNS is stimulated by peptides that trigger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 54 publications
(1 reference statement)
7
120
0
Order By: Relevance
“…Nuclear IB proteins are also known to form a complex with NF-B p52, a protein homologous to p50 (7,12,37). As expected from the homology, in vitro complex formation with p52 was impaired by threonine substitution for the invariant aspartate in ANK1 of nuclear IBs: Asp-451 in IB, Asp-60 in IB NS , and Asp-127 in Bcl-3 ( Fig.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Nuclear IB proteins are also known to form a complex with NF-B p52, a protein homologous to p50 (7,12,37). As expected from the homology, in vitro complex formation with p52 was impaired by threonine substitution for the invariant aspartate in ANK1 of nuclear IBs: Asp-451 in IB, Asp-60 in IB NS , and Asp-127 in Bcl-3 ( Fig.…”
Section: Resultsmentioning
confidence: 63%
“…The ARD of IBs mediates the association with NF-B dimers via direct binding to the NF-B Rel homology region (23,33,34). Although the ARD of nuclear IBs displays a high sequence similarity to that of cytoplasmic IBs except for the additional seventh motif ANK7 (10,12,35,36), the preference for NF-B dimer species differs between the nuclear and cytoplasmic IBs, as described above (7-9, 12, 16, 37). Furthermore, there exists a difference in interaction with B DNA.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This study was performed with a new IkB family member (IkBNS) which can be induced by TCR stimulation. 37 The authors showed that NF-kB could be blocked by overexpression of IkBNS, and that this increased anti-CD3e-induced apoptosis of FTOC. Further studies are however necessary to confirm the role of this new IkB protein.…”
Section: Nf-jb and T Cellsmentioning
confidence: 99%
“…52 The authors found that a novel IkB-like NF-kB inhibitor, IkBNS, is upregulated by peptides that trigger negative selection but not by those inducing positive selection (i.e., survival) or nonselecting peptides. IkBNS blocks transcription from NF-kB reporters.…”
Section: Central Tolerancementioning
confidence: 99%